064 Expert consensus on standards for multiple sclerosis care: results from a modified delphi process. Issue 6 (24th May 2018) - Butzkueven, Helmut; Hobart, Jeremy; Bowen, Amy; Eberhard, Lucy; Pepper, George; Giovannoni, Gavin
Abstract : Introduction: The importance of prompt intervention in multiple sclerosis (MS) was described in the widely endorsed report, Brain health: time matters in multiple sclerosis . 1 The present study aimed to define standards for the timing of key steps in the care pathway. Methods: An international group of 29 MS neurologists was recruited from regions with high MS prevalence to participate in a modified Delphi process. Across five rounds, they defined 'core', 'achievable' and 'aspirational' time frames (to reflect a minimum, good and high standard of MS care, respectively). A 31-member Reviewing Group of MS nurses, experts with MS and allied healthcare professionals reviewed the results and provided feedback to four Chairs. Results: Consensus was reached (≥75% agreement; n=21) on core, achievable and aspirational time frames for events spanning the MS care pathway. Here, we will present 21 achievable standards related to referral, diagnosis, treatment decisions, monitoring and managing new symptoms. For example, the Panel agreed that most MS teams should be aiming to 1 complete a diagnostic workup for MS within 4 weeks of a patient being referred to a neurologist, 2 assess patient eligibility for a suitable disease-modifying therapy within 3 weeks of diagnosis, 3 perform follow-up clinical evaluations every 6 months, and 4 offer an annual MRI scan. Conclusion: These standards will inform tools for clinics and people with MS and act as a potential future benchmark for established and developing MS clinics across the globe aiming to deliver the highest quality care. Reference: . Giovannoni G, et al. Mult Scler Relat Disord2016;9(Suppl 1):S5–S48.